The Effect of Blended Learning (b-learning) on Developing Vocabulary and Reading, A Study in the First Level of Credits Course in the Faculty of Medicine of the University of Cuenca, during the school year 2014-2015. - Palacios Cecilia, Raquel (2016)
Using an approach that integrates technology to broaden and to reinforce what was learnt in class catches attention, particularly if this approach is used to promote a foreign language learning. The present study involves the use of Blended Learning Approach, which is an updated approach that integrates face-to-face and online instruction. The objective of this study was to determine the effect of blended learning on the development of vocabulary and reading in students of first level. For this purpose, it was necessary to examine three questions: Does the application of active techniques in face-to-face instruction improve vocabulary and reading? Does the implementation of interactive activities in a Moodle course improve vocabulary and reading? What is the students’ level of satisfaction regarding the blended learning implemented? To analyze these questions, it was developed and applied activities taking into account active techniques and strategies and it was also designed a Moodle course. Indeed, the techniques and strategies applied in the face-to-face sessions and the activities in Moodle improved vocabulary and reading significantly. Besides, the blended learning implemented caused high level of satisfaction in students. These findings suggest that a Blended Learning Approach that includes techniques, strategies, and activities on Moodle enhances lexis and reading and also provides great satisfaction in students. However, this study needs to be applied to a bigger population.